Application of the Welfare Quality® assessment system on European beef bull farms. (17th April 2014) - Kirchner, M. K.; Schulze Westerath, H.; Knierim, U.; Tessitore, E.; Cozzi, G.; Pfeiffer, C.; Winckler, C.
<x content-type="archive" xml:space="preserve">Abstract</x> Welfare concerns for intensive beef production have often been raised, but on-farm welfare assessment studies are rare. The aim of this study was to apply the Welfare Quality® (WQ) welfare assessment system for fattening cattle on beef bull farms to evaluate the state of welfare at the level of WQ measures and of aggregated scores, as well as overall classification. In addition, the purpose was to evaluate two ways of providing feedback information to the farmers with regard to possible welfare improvements on the farms. The study was conducted in Austria, Germany and Italy on a total of 63 beef bull farms with deep litter or cubicle-housing systems. Assessments were carried out 3 times (1 month and 7 months apart from the initial visit). In every country, farmers were assigned to two treatment groups (feedback from initial visit as written report, F, written feedback plus oral advice, FA) and a control group (C), which did not receive any feedback. At the criterion level, the highest average welfare scores were obtained from 'Absence of prolonged hunger' (94/100 points) followed by 'Absence of pain induced by management procedures' (88/100) and 'Comfort around resting' (77/100). Most welfare concerns related to the criteria 'Absence of disease' (40/100), 'Expression of social behaviour' (44/100) and 'Positive emotional state' (48/100), thus indicating room for improvements. Two-thirds of the farms achieved the 'Enhanced' level, about one-third was judged 'Acceptable' and only one farm 'Excellent'. After 6 months of monitoring period, there was no significant welfare improvement in both the treatment groups as compared with the control group. Reasons for the lack of effect may mainly be seen in the short monitoring period and a lack of external incentives. In conclusion, the WQ assessment system revealed areas for improvement, but longer term studies and investigations on alternative ways of transferring outcomes from on-farm welfare assessments to farmers should be carried out in future.